AGV scheduling and routing for automated container terminals - Xu, Yan (2016)
Routing and scheduling for Automated Guided Vehicles (AGVs) between the vessels and the storage yard is investigated. AGVs are constrained to move in a predefined network of roads and changing their locations over time. AGVs are continuously assigned a transportation task with a deadlines, once the previous task is completed. Given such an environment, a path planner algorithm is presented to find a collision-free and deadlock-free route in the network that takes the AGV from a given start node to a destination node in minimum time. Our scheduler selects the AGV to be planned in an appropriate order to minimize tardiness in delivering containers. The problem is solved by: (1) dynamic path planning algorithm using a space-time spanning tree, and (2) scheduler using sliding window. Algorithms for the two sub-problems are presented and experimental results of the algorithms is analyzed